Concentration-Effect Relationship after Intravenous Hydromorphone Administration: Use of An Effect Compartment Model and System Analysis to Minimize Hysteresis of Effects - D Westerling; P Hoglund (Pain Research and Management)
OBJECTIVE: To investigate the concentration-effect relationship of hydromorphone by using two different methods to minimize the hysteresis between concentration and effects.